Zu Besetzungsmöglichkeiten des linken Feldes im Deutschen und im Polnischen. Eine kontrastive Analyse der gesprochenen Sprache dargestellt am Beispiel der Talkshow - Piosik, Michał (Wydział Neofilologii UAM w Poznaniu, 2016)
The aim of the present thesis is to compare and contrast all possible syntactic realizations of the preverbal topological filed in spoken German and Polish. The point of departure for this corpus-based study are the model of linguistics analysis of Darski (1987, 2010) and the topological field model which is a well-known and tried approach for describing of syntactic relations in the German language. Against the background of the research goals of the thesis, the topological model has been slightly modified and adapted for the Polish language. The analysis which takes into consideration both topological, prosodic and pragmatic characteristics was achieved by examination of altogether four transcripts of popular German and Polish talk shows, which contain approximately 1600 transcript segments and were generated for the purposes of this inquiry.
Keywords: niemiecko-polska składnia kontrastywna; lingwistyczny model analizy Darskiego; polski i niemiecki język mówiony; język w audycjach talk-show; konwencja transkrypcyjna GAT2; program do transkrypcji FOLKER; contrastive English-Polish syntax; Darski’s model of linguistic analysis; spoken German; spoken Polish; language in talk-shows; transcription convention GAT2; transcription software GAT2; deutsch-polnische kontrastive Syntax; das linguistische Analysemodell von Darski; gesprochenes Deutsch; gesprochenes Polnisch; Sprache in Talk-shows; Transkriptionskonvention GAT2; Transkriptionssoftware FOLKER